DUNALIELLA SALINA IMPROVED OBESITY-ASSOCIATED INFLAMMATION AND OXIDATIVE DAMAGE IN ANIMALS’ RODENT - El-baz, Farouk K; Aly, Hanan F; Fayed, Dalia B (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to investigate the efficacy of microalgae Dunaliella salina to improve apelin, oxidative damage, inflammatory, and apoptotic function implicated in high-fat diet (HFD)-induced obesity in rats. Methods: Fifty male Westar albino rats weighing 150â€“160 g were fed on HFD for 12 weeks. Treatment of obese rats with D. salina was carried out in a dose 150 mg/kg body weight as compared to orlistat as anti-obesity standard drug. Blood nuclear factor kappa-B cells (NF-kB), apelin, apoptosis regulator (B-cell lymphoma 2 [BCl2]), monocytes chemo attractant protein-1, paraoxonase-1 (PON1) were determined in serum of different groups. Besides, lipid peroxidation (malondialdehyde [MDA]), glutathione (GSH) levels as well as histopathological examination were investigated in liver tissue of obese rats. Results: Serum apelin, MDA, and NF-kB levels were significantly high, reached to 97.25, 158.18, 511.433, and 170.73%, respectively. While significant decrease in PON1 (47.82%), BCl2 (74.88%), and GSH (63.54 %), levels were detected in the obese rats compared to controls. Obviously improvement in all biomarkers under investigation upon treated obese rats with ethanol extract of D. salina. Histopathological examination of obese hepatic tissue showed dilatation in the central portal veins associated with inflammatory cells infiltration in the portal area and congestion. However, treatment of obese rats with D. salina confirmed biochemical analysis and declared less diffuse inflammatory cells infiltration as well as less focal infiltration in both hepatic parenchyma and portal area with higher improvement in D. salina than drug. Conclusion: It could be concluded that D. salina has a great ability to improve inflammation associated with obesity as well as damaged hepatic architectures which can be used as a promising anti-obesity nutraceuticals.